Depressão em adultos residentes em comunidades quilombolas de Vitória da Conquista (BA) - Sabrina Martins Barroso (2014)
Introduction: Quilombolas are African-descendants with a high degree of social vulnerability. They are descendants of slaves who live in rural and extremely poor areas with poor infrastructure and limited access to health services. However, there are few studies about their health and the prevalence of depression in this population is unknown. This studyhad three objectives: 1. To investigate the discriminative ability and the difficulty of the items from Patient Health Questionnaire (PHQ-9) to identify depressive symptoms in quilombola population; 2. To estimate the prevalence of depression in quilombola communities in Vitória da Conquista (BA); and 3. To identify associated factors with depression in this population. Methods: Population-based cross-sectional survey of 764 participants randomly selected from five quilombola communities from Vitória da Conquista County (BA), Brazil. Depression was defined by 10 or more points and the presence of five or more symptoms most of days during the last 15 days using PHQ-9 scale. For the objective 1 discriminative and difficulty of the items of PHQ-9 was analyzed by Item Response Theory. For the second objective, we estimated the prevalence of depression dividing the number of people who scored > 10 points in the PHQ-9 and five or more symptoms by the total people. For the third objective we used Poisson regression with robust estimators toestimate the prevalence ratio (PR) with 95% confidence interval (95%CI) for the variables associated with the depression for the total population and logistic regression to estimate the odds ratio (OR) and 95%CI, separately, for each sex. Results: The items of the PHQ-9 showed the ability to discriminate between moderate and very high. The item about feeling of hurting oneself and death showed the greatest discrimination ability. The item with the lowest discrimination refers to feeling depressed. The prevalence of depression was 12% (95%CI 10% - 14%), but only 2.3% of people reported a previous diagnosis. Screening fordepression was associated with self-rated poor or very poor health (PR = 1.14, 95%CI 1.04 - 1.26), chronic diseases (PR = 1.08, 95%CI 4.1 - 1.13), physical inactivity (PR = 1.06, 95%CI 1.01 - 1.11) and fair access (PR = 1.07, 95%CI 1.01 - 1.13) or poor to health services (PR = 1.07, 95%CI 1.02 to 1.12). Factors associated with depression differed between menand women. Among men, factors associated with depression were previous diagnosis of chronic illness (PR = 5.1. 95%CI 1.8 14.8), self-perception of health assessment as poor/very or poor (PR = 2.3. 95%CI 1.1 5.1), and poor access to health services (PR = 1.9.95%CI 1.1 4.1). Among women, factors associated were: previous diagnosis of psychiatric disorder (PR = 2.4. 95%CI 1.2 4.8), self-perception of health assessment as poor/very or poor (PR = 2.4. 95%CI 1.1 4.8), current or previous smoking history (PR = 1.9. 95%CI1.2 3.2) and those who declared themselves as non-black (PR = 1.5. 95%CI 1.3 1.9). Conclusions: The prevalence of depression in this quilombola population was similar to the Brazilian general population and factors associated with depression were similar to those identified in other vulnerable populations. Furthermore, the PHQ-9 showed to be a useful tool for screening depression in quilombola populations. Public actions to combat social and health inequalities needs be implemented, focusing on the condition of social vulnerability in quilombola population and early screening for depression.